GEOCHEMICAL EVALUATION OF CRUDE OILS IN THE LLANOS ORIENTALES BASIN - Moyano Montaña, Julian Camilo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2023)
The area of the present study is located in the Llanos Orientales basin, in which the main objective was a geochemical evaluation of crude oil in the geological and production provinces: Piedemonte, Arauca, Casanare and Meta-Vichada based on related information about bulk parameters, gas chromatography and biomarkers. The data for each of the provinces were analyzed and reorganized according to the geological formation corresponding to the reservoir rock indicated for each crude oil sample, from which 576 crude oil samples were obtained with the information that allowed relating some petroleum compounds and defining the depositional environments of the source rock facies of crude oil, identify biodegradation processes and mixtures of crude oils. In the same way, maps were made where the crudes were classified according to their quality. It was established that the best quality crudes belong to the Piedemonte sector in the Mirador Formation. On the other hand, the sector where the crudes show lower quality corresponds to Meta-Vichada in the San Fernando Formation. This analysis was carried out for the four provinces, obtaining key information for future exploratory campaigns in the Llanos Orientales basin, taking into account that it is the richest basin in hydrocarbons in Colombia.